BATAS USIA PERKAWINAN DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Nur Hikmah; Ach Faisol; Dzulfikar Rodafi (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2020)
Abstract Marriage is a way to validate the bond between men and women in a sacred bond so that they become a husband and wife. The purpose of marriage as stated in the Marriage Law article 1, paragraph 1, is to form a family or household that is endangered and based on a Godhead. In deciding a marriage. It is not a benchmark if you are ready and able to get married. Age is one of the material requirements for a marriage, a material requirement is a condition that is related to the core or principle in a marriage in general. Regarding the age limit of marriage, in positive law refers to the Marriage Law article 7 paragraph 1 of 1974 which was later revised and became Marriage Law No. 16 of 2019. Then in Islamic law there is no argument in the Koran or Hadith that states how many restrictions marriage age. This then causes the scholars to give different interpretations of the age limit of marriage. Keywords : Marriage, Minimum age,